O jogo acabou: um estudo socioantropológico sobre o fim da trajetória profissional de atletas do futebol - Guimarães, Arthur Silveira (2017)
This proposal of work is directed to the moment of transition of the sports career of footballer, linked to the end of the professional trajectory, to a new experience of biographical relocation. Considering the impact that the end of a professional career causes in any individual, we propose to identify and analyze the sports career of soccer athletes who face the transition from high - performance professional sport to the post - football moment, that is, . In this perspective, we seek to understand the organizational and social processes involved in this stage of the professional career of these footballers. For this, we made a specific cut of the field of professional performance of the ex-athletes interviewed. Thus, this research is directed to former athletes who played in Northeastern football, specifically in Paraíba football. Using ethnobiography as a research tool, we analyze the subjectivities and reflections of the subjects involved (ex-athletes), their identity transformations as possibilities of understanding the act of moving away from soccer fields.